The consumption response to labour income changes - Kris Boudt; Koen Schoors; Milan Van Den Heuvel; Johannes Weytjens (National Bank of Belgium, 2022)
We develop an income shock classification taxonomy that classifies income changes into 9 categories based on the magnitude, direction and permamency of the income change. Using 01/2017 - 06/2022 bank transaction data of Belgian employees and workers, we apply this classification on labour income changes to find that the elasticity to a positive recurrent labour income shocks is almost double that of a regular labour income change and a transient positive labour income shock. The effect significantly varies among different consumption durability types and is amplified in case of low levels of liquid wealth. Accounting for the heterogeneity in types of income changes is therefore important to understanding the multiplier effect of fiscal policy aimed at increasing available income.
Keywords: 330; Income changes; consumption; liquid wealth; marginal propensity to consume